2023
DOI: 10.1007/s12079-023-00788-1
|View full text |Cite
|
Sign up to set email alerts
|

Unpacking the complexity of nuclear IL-33 (nIL-33): a crucial regulator of transcription and signal transduction

Zengbin Wang,
Nanhong Tang

Abstract: Small ubiquitin-related modifier USP21 Ubiquitin-specific peptidase 21 SMAD3 Smad family member 3 TSLP Thymic Stromal Lymphopoietin hBD2 Human beta-defensin 2 GATA3 GATA-binding protein 3 HDACs Histone deacetylases PARP1 (ADP-ribose) polymerase 1 ATM Ataxia-telangiectasia mutated BER Base excision repair DSB DNA double-strand break DDR DNA damage response DDIT3 DNA damage-inducible transcript 3 TNF-α Tumor necrosis factor-α,SASP,senescenceassociated secretory phenotype PROTACs Proteolysis-targeting chimeras DU… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 97 publications
0
4
0
Order By: Relevance
“…Recent studies have begun to survey full-length IL-33 as a possible initiator of noncanonical, ST2-independent signaling, mostly examining its effects on epithelial cells and fibroblasts [58,59]. These noncanonical, ST2-independent signaling actions of full-length IL-33 have also been attributed to its function as a transcription regulator of the p65 subunit of the NF-κB complex [60,61]. Interestingly, a study from Hussey et al has indicated full-length IL-33 can direct macrophage differentiation towards a M2 phenotype [62], which studies have shown to be expanded during normal pregnancy and impaired during PE [63].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have begun to survey full-length IL-33 as a possible initiator of noncanonical, ST2-independent signaling, mostly examining its effects on epithelial cells and fibroblasts [58,59]. These noncanonical, ST2-independent signaling actions of full-length IL-33 have also been attributed to its function as a transcription regulator of the p65 subunit of the NF-κB complex [60,61]. Interestingly, a study from Hussey et al has indicated full-length IL-33 can direct macrophage differentiation towards a M2 phenotype [62], which studies have shown to be expanded during normal pregnancy and impaired during PE [63].…”
Section: Discussionmentioning
confidence: 99%
“…IL-33 plays a protective role against parasites by promoting the recruitment, amplification, and maturation of neutrophils and eosinophils. It can exist in three forms: full-length IL-33 (FLIL-33), secreted soluble cytokine IL-33 (sIL-33), and nuclear IL-33 (nIL-33), with different implications in tumor immunity that can vary depending on the tumor histotype [22][23][24].…”
Section: Il-1 Family Cytokinesmentioning
confidence: 99%
“…Interleukin 33 (IL-33), initially identified as a nuclear factor in high endothelial venules (NF-HEV) (1), is structurally related to the cytokines of the IL-1 family and it is expressed by fibroblasts, endothelial and epithelial cells, among other cell types (2). The full-length human IL-33 precursor encompasses 270 amino acids, featuring an N-terminal region that includes a chromatin binding motif and a nuclear localization signal (amino acids 1-65), a sensor domain from amino acid 66 to 111, and a C-terminal IL-1-like cytokine domain (amino acids 112-270) that gives IL-33 its cytokine-like properties (3).…”
Section: Introductionmentioning
confidence: 99%
“…The full-length IL-33 molecule of 33 kDa can be found in the nucleus and retained there (1). When cellular injury occurs, IL-33 is released and processed to a mature form by protease cleavage (2). The mature form of IL-33 has a high affinity to the ST2 receptor.…”
Section: Introductionmentioning
confidence: 99%